INTERAKSI ANTARA SENSASI DAN PRESEPSI DALAM PEMBENTUKAN PENGALAMAN MANUSIA DI LINGKUNGAN SEKITAR - Fabiano Christian Adolf Kontu; Richard Luas; Prishicha Tumewu; Filipi Pattyranie; Jesica Binalu; Praysi Maleke; Allani Briel (PT. Giat Konseling Nusantara, 2026)
This study discusses how human experiences with the environment are formed through a process that simultaneously involves sensation and perception. Sensation is the initial stage when the senses receive physical stimuli from the environment, while perception interprets and gives meaning to these stimuli so that the experience becomes complete and meaningful. This article aims to explain how the interaction between sensation and perception plays a role in shaping human experience, as well as the factors that influence it. Through a literature review of various cognitive psychology studies, it was found that a person's experience is strongly influenced by biological conditions, attention, previous experiences, and social context. These findings indicate that human experience is not simply the result of receiving stimuli, but rather an active process influenced by how individuals interpret information. This complex interaction between sensation and perception is what makes each individual's experience of the environment unique and different. This study uses a descriptive qualitative approach to describe how sensation and perception work together and the challenges that arise in the process of understanding the environment.